KEMAMPUAN PROFESIONAL GURU DALAM MENDIAGNOSIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VIII DI MTS MIFTAHUL KHAIRIYAH KOTO BARU - lasmawati lasmawati; Andrizal Andrizal; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2020)
This study aims to describe the learning difficulties of students in Al-qur’an Hadits subjects, Know the professional abilities of teachers in diagnosing student learning difficulties, And know the teacher’s constraints in diagnosing student lerning difficulties on Al-qur’an Hadits subjects.This Study uses a qualitative approach with a descriptive type of research, with data collection techniques through observation, interviews and documentation. And data analysis techniques used are reducing data, presenting data and drawing conclusions.The result of this study indicate that overall the techers has done his ability in diagnosing student learning abilities in subject Al-qur’an hadits of class VIII MTs Miftahul Khairiyah Koto Baru. This is indicated by: (1) The teachers indetifies students who have lerning difficulties, (2) the teacher localizes the types of learning difficulties, (3) the teacher detects the cause of lerning difficulties, (4) and teacher does the process of solving student’s learning difficulties.